Sprint velocity and step frequency during repeated sprint ability testing are associated with high-intensity locomotor activity in elite female field hockey - Carlos Rivera; Pablo González-Frutos; Fernando Naclerio; Javier Mallo; Santiago Veiga (PLoS ONE, 2026)
Field hockey is an intermittent, high-intensity team sport in which global positioning system (GPS) monitoring and field-based fitness testing are widely used; however, the relationship between repeated sprint ability (RSA) determinants and match physical demands remains unclear. This study examined the association between RSA kinematic variables (sprint velocity, step frequency, and step length) and GPS-derived locomotor activity metrics during elite female field hockey matches. Fourteen elite female field hockey players (all members of a first team competing at the highest national and European level) completed a linear RSA protocol consisting of six 30-m maximal sprints interspersed with 30 s of active recovery. External load was quantified during four official competitive matches played against top-level opponents (teams ranked in the top four of the national league or National Cup semi-finalists) within three weeks of testing using 10-Hz GPS devices. RSA sprint-velocity metrics showed very large correlations (r > 0.70, p < 0.01) with match performance variables as total sprint distance, sprint distance per minute (sprint·min - ¹), high-speed running per minute (HSR·min - ¹) and high-intensity accelerations (>3 m·s -2 ·min ⁻ ¹). Step frequency also demonstrated very large associations (r > 0.70, p < 0.01) with sprint, sprint·min - ¹, HSR·min - ¹, and maximal acceleration, whereas step length was not significantly related to any match variable. These findings indicate that RSA performance, particularly sprint velocity and step frequency, is associated with high-intensity match demands in elite female field hockey. RSA testing may therefore represent a practical, low-cost tool for monitoring or approximating GPS-derived locomotor activity during competitive matches.